Synthesis of Heterocycles in Contemporary Medicinal Chemistry - Časar, Zdenko; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2016)
The series Topics in Heterocyclic Chemistry presents critical reviews on present and future trends in the research of heterocyclic compounds. Overall the scope is to cover topics dealing with all areas within heterocyclic chemistry, both experimental and theoretical, of interest to the general heterocyclic chemistry community. The series consists of topic related volumes edited by renowned editors with contributions of experts in the field. All chapters from Topics in Heterocyclic Chemistry are published Online First with an individual DOI. In references, Topics in Heterocyclic Chemistry is abbreviated as Top Heterocycl Chem and cited as a journal.
Development of a Manufacturing Process for the Formation of a Nucleoside Drug Candidate -- Development of Efficient Routes to Access C-Glycosides as SGLT-2 Inhibitors for the Treatment of Type 2 Diabetes -- Synthetic Routes to Sofosbuvir -- Synthetic Challenges in the Assembly of Macrocyclic HCV NS3/NS4A Protease Inhibitors: The Case of BILN 2061 and Its Analogs -- Recent Progress in the Synthesis of Super-Statins -- Development of Synthetic Routes to Dolutegravir -- Story of Eribulin Mesylate: Development of the Longest Drug Synthesis.
Keywords: Medicinal chemistry; Chemistry, Organic; Analytical chemistry; Medicinal Chemistry; Organic Chemistry; Analytical Chemistry